PERSEPSI MAHASISWA TERHADAP AKUNTANSI STUDI KASUS: MAHASISWA FTIK - Hendra F Santoso; Daniel Widjaja (Jurnal Akuntansi, 2013)
AbstractIn Academic Year 2012/2013 FTIK provide TEK 2020 Introduction to Accounting course to its students . Accounting course is a new thing for students , these course is expected become useful for graduates in order to work at the company. The purpose of this study was to obtain an overview of the students’ perceptions of accounting .This study uses descriptive method where information collected through the use of questionnaires with a Likert scale refers to the scale of 1-5 and distributed online using the “ Google Form “ . The population in this study were63 respondents whose all students of FTIK Academic Year 2012/2013 which took Introduction to Accounting course.The results showed that students’ perceptions of motivation to become an accountant is not too big but they tend to like accounting because accounting interesting and was happy when her family members become accountants . Student perceptions of the accountant’s job looks less attractive , they consider accountant job was boring , because working alone , huddled numbers so just got a little satisfaction but they tend to disagree when people say that accountants are boring and realized many professional accountants interact with people . student perceptions about the awards on the accounting profession is quite high and the accounting profession considers honorable, but still below other professions.Keywords : Accounting, Student Perception863